Microglia as therapeutic target in central nervous system disorders - Oluwaseun Fatoba; Takahide Itokazu; Toshihide Yamashita (Elsevier, 2020)
Chronic microglial activation is associated with the pathogenesis of several CNS disorders. Microglia show phenotypic diversity and functional complexity in diseased CNS. Thus, understanding the pathology-specific heterogeneity of microglial behavior is crucial for the future development of microglia-modulating therapy for variety of CNS disorders. This review summarizes up-to-date knowledge on how microglia contribute to CNS homeostasis during development and throughout adulthood. We discuss the heterogeneity of microglial phenotypes in the context of CNS disorders with an emphasis on neurodegenerative diseases, demyelinating diseases, CNS trauma, and epilepsy. We conclude this review with a discussion about the disease-specific heterogeneity of microglial function and how it could be exploited for therapeutic intervention.